Problem-frame-oriented requirements traceability to enhance requirements management - Shengwen, Xiao; Hassan, Sa'adah; Che Pa, Noraini (Politeknik Negeri Padang, 2024)
Managing software requirements is a challenge in software development and maintenance. Requirements changes are inevitable, particularly in a rapid iterative development approach that leads to occasional changes in software requirements. Unable to manage this properly will impact the overall quality of the software. Thus, requirements traceability is essential because it ensures that all requirements are adequately addressed, changes are managed effectively, and that there's a clear linkage between business requirements and the system's functionality. Inadequate traceability mechanisms can make changing the requirements and detecting their impact difficult. Thus, it is crucial to establish precise requirements traceability and maintain clear links to manage the requirement changes effectively. Our research explores using a problem frames modeling approach to address this issue. It starts by representing requirements as problems, creating a requirements relationship diagram, and generating a corresponding relationship matrix. The values in the traceability matrix help identify which elements are most affected by requirement changes, allowing developers to prioritize changes that minimize overall system impact. Furthermore, using problem frame modeling, complex problems can be broken down into manageable sub-problems, providing a clear structure for understanding the requirements. Additionally, a tool has been created to streamline the process, and a case study is used to demonstrate the functionalities. An evaluation has been conducted to assess the usability of the proposed work. The requirements relationship diagrams and relationship matrices visually and quantitatively map the links between requirements, enabling traceability and identifying the impact of changes in requirements.